Design of the 'SI ULET' Accounting Information System for Quick Calculation of Merchandise Inventory at AtariaShop Plastic Houseware Bandung Barat - Rheima Fritania Andami; Tiris Sudrartono; Cahyadi Agustin (Indonesian Journal of Economics and Management, 2023)
Accounting information systems are very important to business activities. The amount of merchandise inventory owned by the company must be monitored for its availability because it is sold for profit. It is known that AtariaShop Plastic Houseware still uses a manual system to calculate its merchandise inventory. This causes the calculation of merchandise inventory to be slow, and the resulting information is often inaccurate. The qualitative approach method was used by the researchers in this study. Assisting in the calculation of computerized merchandise inventory requires the design of an accounting information system named SI ULET. This system as a whole displays the final report in the form of merchandise stock cards. SI ULET is proven to help business activities run effectively because this system can display the mobility of in-out merchandise due to purchases and sales so that the amount of merchandise inventory in stores can be quickly identified.